Abrogation of glutathione peroxidase-1 drives EMT and chemoresistance in pancreatic cancer by activating ROS-mediated Akt/GSK3β/Snail signaling. Issue 44 (1st November 2018) - Meng, Qingcai; Shi, Si; Liang, Chen; Liang, Dingkong; Hua, Jie; Zhang, Bo; Xu, Jin; Yu, Xianjun
Abstract The devastating prognosis of pancreatic ductal adenocarcinoma (PDAC) is partially attributed to chemotherapy resistance. Glutathione peroxidase-1 (GPx1) plays various roles in the development and progression of multiple tumors, with the exception of pancreatic cancer. Here, we tentatively explored the role of GPx1 in the malignant biological behavior and gemcitabine (GEM) resistance of PDAC. GPx1 levels were detected using tissue microarrays and were negatively correlated with the overall survival of patients with PDAC. GPx1 silencing induced a mesenchymal transition phenotype and increased GEM resistance in vitro and in vivo. Additionally, the activation of reactive oxygen species (ROS)-mediated Akt/glycogen synthase kinase 3β (GSK3β)/Snail signaling was involved in this process, as determined by RNA sequencing. Moreover, low GPx1 expression correlated with a worse survival rate in patients with PDAC who received GEM adjuvant chemotherapy, whereas this correlation was not detected in patients receiving fluoropyrimidine. Based on our results, GPx1 inhibits the epithelial–mesenchymal transition (EMT) and chemoresistance by regulating the Akt/GSK3β/Snail signaling axis in PDAC. Furthermore, GPx1 may be a potential predictive biomarker in GEM-treated PDAC patients.